Studying The Impact of Bank Credit Management Policy Indicators on The Profitability Rate of Private Banks Operating in Syria - غضبان, عبادة (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aims to point out the factors affecting the profitability of banks in a theoretical manner, clarify the concept of cross-sectional series, and study the impact of bank credit management policy indicators on profitability rates. The descriptive analytical approach was adopted and the study covers the period from 2011 to 2021. The secondary data necessary for the purposes of the study was obtained from the financial statements of all traditional private banks operating in Syria as a whole. Among the most important results, there is a positive, statistically significant effect for both the ratio of net facilities/total deposits and the ratio of shareholders’ equity/net facilities in operating Syrian banks on the rate of return on total assets, while there is a negative, statistically significant effect for the ratio of net facilities/total assets in Syrian banks. operating in the rate of return on total assets, but there is no statistically significant positive effect of the ratio of net interest on facilities/total income in Syrian banks operating in the rate of return on total assets